2020
DOI: 10.1007/s11914-020-00592-5
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Human Locomotion to Inform Exercise Prescription for Osteoporosis

Abstract: Purpose of Review We review the literature on hip fracture mechanics and models of hip strain during exercise to postulate the exercise regimen for best promoting hip strength. Recent Findings The superior neck is a common location for hip fracture and a relevant exercise target for osteoporosis. Current modelling studies showed that fast walking and stair ambulation, but not necessarily running, optimally load the femoral neck and therefore theoretically would mitigate the natural age-related bone decline, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 95 publications
2
6
0
Order By: Relevance
“… 38 , 39 Thus, the prescribed exercises in the studies included in our analyses probably applied different loads across the femoral neck and other hip regions. 37 , 40 Our subanalyses at the femoral neck also demonstrated that bone loss was attenuated by exercise in adults aged ≥60 years but not in those aged <60 years. Exercise may, therefore, be particularly important for older adults with overweight and obesity when undergoing diet-induced weight loss, and this is supported by the evidence that weight loss is associated with increased likelihood of fractures in older populations.…”
Section: Discussionmentioning
confidence: 58%
“… 38 , 39 Thus, the prescribed exercises in the studies included in our analyses probably applied different loads across the femoral neck and other hip regions. 37 , 40 Our subanalyses at the femoral neck also demonstrated that bone loss was attenuated by exercise in adults aged ≥60 years but not in those aged <60 years. Exercise may, therefore, be particularly important for older adults with overweight and obesity when undergoing diet-induced weight loss, and this is supported by the evidence that weight loss is associated with increased likelihood of fractures in older populations.…”
Section: Discussionmentioning
confidence: 58%
“…Therefore, it appears that exercise can have a remarkable effect on strength despite inducing a relatively modest BMD response. Yet, the optimal exercise type and amount for optimal hip strength in each participant remains to be determined (Martelli et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Preventative solutions may help understanding the causes and mitigate the burden of hip fracture. As aging typically leads to reduced bone mass particularly in bone regions subjected to infrequent (unusual) motor tasks, these observations may help explaining the beneficial effect of odd-impact activities on hip health [34] , the decreased prevalence of hip fracture in societies with higher and more variable activity levels [7] and, as part of our society's drive for healthy ageing, exercise treatments to promote bone health [35] . For example, a new generation of anabolic treatments, alongside the traditional anti-resorptive treatments, may be able to specifically target femoral regions of most pronounced bone loss in frail people.…”
Section: Discussionmentioning
confidence: 99%